(3GdeYLes - (3CHh GdMSf eMeO Hf CMeO Hf eMeO GdUjOGhj GdZSGfj, GHf LejY,J (B402 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg HMSc Efi QCjJ GdfHi Udi Gddg Ydjg hSde ai Gdfhe ade Cbd dg GOY Gddg di hbdJ jG QShd Gddg s
(3BNQgG (B:s
(3MOKfG GHf GdQHjY HHZOGO hgh GdMSf Hf CMeO , MOKfG YeQ Hf THI Yf GdRgQi Cf GdfHi Udi Gddg Ydjg hSde cGf jbQBgG (B: (3eGdc BNQ cJGH GdeYLe dGHf LejY s
(3cJHJ HNW bOje LOkGs
(3fbdJ gPg GdfSNI ef CUd Ydjg SeGYGJ HYVgG Ydi GdMGaX GdbGSe Hf Ydi Hf gHI Gddg GdTGaYi SfI (B599 (3hHYVgG Ydi CHj GdMSf Hf GdeSde Hf eMeO GdSdei GdeYQha HGHf GdTgQhRQi SfI (B465s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B313s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdJGQjNs